Systemic angiogenic protein changes following propranolol therapy in infantile hemangioma: a multi-target perspective - Liang, Lijun; Zhang, Yan; Ma, Yan; Liu, Jing; Du, Wangnan; Ma, Qiang (Frontiers in Pharmacology, 2025)
IntroductionInfantile hemangioma (IH) is a common benign vascular tumor in infants, often requiring intervention due to potential functional impairment and cosmetic concerns. Propranolol, a nonselective β-adrenergic receptor blocker, is the first-line therapy for IH, yet its mechanisms remain incompletely elucidated.MethodsThis prospective study investigated the systemic angiogenic protein profile changes in response to propranolol in 14 treatment-naïve IH infants compared to 14 healthy controls using antibody array analysis.ResultsWe identified twenty-six angiogenic proteins significantly downregulated in pretreatment IH patients compared to healthy controls. After 3 months of propranolol treatment, six proteins including HB-EGF, TGFα, ANGPTL4, Follistatin, Tie-1 and PLGF were significantly upregulated. Bioinformatic enrichment analysis revealed that these proteins are involved in key biological processes and signaling pathways, including epithelial cell proliferation, angiogenesis regulation, VEGF signaling, ERBB-EGFR axis, Ras-MAPK, and PI3K-Akt pathways.DiscussionThese results suggest that propranolol treatment is associated with a rebalancing of dysregulated angiogenic proteins in IH, through modulating both pro- and anti-angiogenic factors to rebalance vascular homeostasis. Our study provides novel insights into the systems-level pharmacological actions of propranolol and proposes potential biomarkers for treatment response evaluation.